Advancing One Health capacities in Mozambique: A case study of COHESA - Araújo, Lucinda de; Chongo, Inocêncio; Magaia, Vlademiro; Gatambire, Aline; Sacarlal, Jahit; Sumbana, José; Tivane, Almiro; Maholela, Plácida; Inlamea, Osvaldo; Caron, Alexandre; Knight-Jones, Theodore J.D.; Richards, Shauna; et al. (CAB International, 2024)
One Health (OH) concept recognizes the interconnectedness of human, animal, environmental and plant health, and the need for collaboration across these sectors to address health challenges. Mozambique is a southern African country and faces a range of health challenges that can benefit from an OH approach. Publications on research and innovation related to OH in Mozambique have been increasing in recent years indicating the growing interest and support to work on OH. Mozambique has developed various policies and frameworks that indirectly support OH objectives. These include policies related to public health, animal health, agriculture, environmental conservation, and disaster management. While these policies may not explicitly mention OH, they often have overlapping goals, such as disease prevention, environmental protection, and food security. Mozambique has also implemented education and awareness campaigns to control and prevent zoonotic diseases such as rabies and COVID-19. These campaigns include posters and community meetings. In addition to the radio and television broadcasts, Mozambique introduced the OH module for a master’s degree level. The government also partnered with NGOs and other organizations to provide training for farmers and livestock owners on disease prevention and control. To better understand the OH landscape in Mozambique, a baseline assessment was implemented to understand the stakeholders and opinions of OH as it relates to research and innovation, governance, education, and implementation. A series of key informant interviews, alongside a focus group discussion and desktop review, provided the basis for evaluating strengths, weaknesses, and opportunities in OH in Mozambique.